Digital engagement and hospital choice: Exploring healthcare consumers decision-making in the digital healthcare era - Ratnasari, Siwi Dyah; Hariyanti, Tita; Pardiman, Pardiman; Danila, Nevi (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2026)
Digital transformation has reshaped how young consumers evaluate and select healthcare providers, shifting decision-making beyond clinical quality toward digitally mediated experiences and service perceptions. While prior studies have primarily emphasized medical and service-quality factors in hospital choice, limited research has examined how digital engagement and experiential attributes jointly influence healthcare decision-making from a service marketing perspective. This study explores the non-medical determinants of hospital selection in the digital era and examines their implications for healthcare marketing strategy. Using a qualitative phenomenological approach, data were collected through in-depth interviews with 11 young healthcare consumers who had utilized hospital services within the previous two years in Batu City, Indonesia. Thematic analysis identified five key determinants: digital visibility, quality of online interaction, facility comfort, patient reviews, and perceived emotional value. The findings indicate that digital touchpoints and experiential benefits play a central role in shaping service evaluations and provider preferences. This study extends consumer behavior and service marketing literature by integrating digital engagement and perceived emotional value into the understanding of hospital choice. Although the findings are context-specific, they provide insights into how healthcare organizations can strengthen competitiveness through digitally integrated, patient-centered strategies that enhance engagement, satisfaction, and long-term loyalty in increasingly digital service environments.